DFT studies of structural, electronic and optical properties of (5, 5) armchair magnesium oxide nanotubes (MgONTs) - Itas, Yahaya Saadu; Suleiman, Abdussalam Balarabe; Ndikilar, Chifu E.; Lawal, Abdullahi; Razali, Razif; Idowu, Ismail Ibrahim; Khandaker, Mayeen Uddin * (Elsevier, 2023)
Due to high demand for smart materials for use in optoelectronic systems, many experimental studies were carried out on nano systems of magnesium oxide (MgO) such as magnesium nano-wires, magnesium oxide nanoparticles. However, there were reported lack of investigating the electronic and optical response of the nanotube form of MgO across chirality geometry and anisotropic directions. Furthermore experimental studies revealed the properties without taking account in to the chiral effects. Studies of the optoelectronic properties of magnesium oxide nanotubes were not done either experimentally or theoretically. In order to bridge this gap, this work starts with investigating the structural electronic and optical properties of armchair single walled magnesium oxide nanotubes (SWMgONT) on one of the armchair chirality. Calculations were scoped on (5, 5) armchair MgONT with varying inner diameter of 4.2 and 4.5 Å respectively. Although the nanotube is stable in both diameter configurations, MgONT with diameter of 4.5 Å was found be more stable. Studies of the electronic band structure of the 0.62 eV for (5, 5) SWMgONT which is consistent with the experimental values reported. Results from the imaginary dielectric revealed that it becomes transparent above 17.5 eV, Peaks in the energy loss curve are related to intra-band excitations, such that large peaks are associated with Plasmon energy. Based on the values of the first bound excitons (electron-hole) obtained, it can be concluded that (5, 5) SWMgONT is a promising candidate for solar cells and near infrared opto-electronic applications such as biomedical imaging, gas sensing and optical communication.